A robust color image encryption scheme for optical applications using a novel zigzag technique and 3D fractional-order chaotic system - Haddad, Ismail; Belmeguenai, Aissa; Herbadji, Djamel (Oficyna Wydawnicza Politechniki Wrocławskiej, 2025)
In this paper, we present a novel image encryption approach tailored for optical imaging encryption, leveraging fractional-order chaotic systems and an innovative zigzag technique. The proposed scheme employs various zigzag patterns to simultaneously scramble the positions of image pixels, ensuring robust security. The zigzag process is dynamically controlled by a fractional-order chaotic system, which introduces unpredictability and significantly enhances the scheme’s resistance to attacks. The encryption key is derived from the initial values and fractional-order parameters of the chaotic system, offering a substantial improvement over traditional methods that rely on integer-order chaotic systems. This advancement not only expands the key space but also increases the complexity of the encryption process, making it highly secure. The experimental results and security analysis demonstrate the scheme’s effectiveness in thwarting various types of attacks, including brute-force and statistical attacks, particularly in the context of optical imaging systems. These findings highlight the technique’s reliability and suitability for protecting sensitive data in optical imaging applications, where security and precision are paramount. The proposed method represents a significant step forward in securing optical imaging data, providing a robust and efficient solution for modern encryption needs.
Optica Applicata, Vol. 55, 2025, nr 1, s. 117-137
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; fractional-order chaotic systems; zigzag technique; optical imaging encryption; statistical attacks; security analysis; key space